A comparative study on vermifiltration using epigeic earthworm Eisenia fetida and Eudrilus eugeniae. Issue 14 (21st March 2016) - Kumar, Tarun; Rajpal, Ankur; Arora, Sudipti; Bhargava, Renu; Hari Prasad, K.S.; Kazmi, A.A.
Abstract: A comparative study was performed to treat the domestic wastewater through two different epigeic earthworms ( Eisenia fetida and Eudrilus eugeniae ) based vermifiltration unit (VF1 and VF2). Results revealed a significant removal of biochemical oxygen demand (88%), total suspended solids (78%), and total dissolved solids (75%) in the treated wastewater from VF1; while in VF2, it was observed to be 70, 67, and 66%, respectively, at hydraulic loading rate (HLR) of 2.5 m 3  m −2  d −1 . Beside this, a significant reduction of total coliform (3.1 log) was observed in VF1 as compared with 0.98 log reduction in VF2. In addition to this, an increase in earthworm biomass in reactor VF1 was found to be 11.4%; while in VF2, mortality was observed, since the earthworm species E. eugeniae could not survive during the process. Overall, in VF1, the effluent was rich in nitrate, phosphate, and showed the potential of E. fetida for wastewater treatment during vermifiltration process.